2012
DOI: 10.1143/jjap.51.06ff01
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Floating-Gate-Type Metal–Oxide–Semiconductor Capacitors with Nanosize Triangular Cross-Sectional Tunnel Areas for Low Operating Voltage Flash Memory Application

Abstract: Mirage mediation reduces the fine-tuning in the minimal supersymmetric standard model by dynamically arranging a cancellation between anomaly-mediated and modulus-mediated supersymmetry breaking. We explore the conditions under which a mirage "messenger scale" is generated near the weak scale and the little hierarchy problem is solved. We do this by explicitly including the dynamics of the SUSY-breaking sector needed to cancel the cosmological constant. The most plausible scenario for generating a low mirage s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Recently, we have developed FG-type and chargetrapping (CT)-type SOI-FinFET flash memories, and confirmed that the TG structure has a larger memory window and a higher SCE immunity than the DG structure owing to the additional top gate and recessed buried oxide (BOX) region (21)(22)(23)(24). Moreover, we have also demonstrated FG-type split-gate SOI-FinFET flash memories with highly suppressed overerase and experimentally confirmed that nanosize triangular cross-sectional tunnel areas are useful for the fabrication of low-operating-voltage flash memories (25,26). However, the fin channel shape and interpoly dielectric (IPD) material effects on the electrical characteristics of FG-type SOI-FinFET flash memories have not been investigated sufficiently, although the high-k dielectric stacks and barrier-engineered multilayers have been used as an IPD layer for improving the gate coupling of the conventional bulk planar FG-type flash memories (27)(28)(29)(30).…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Recently, we have developed FG-type and chargetrapping (CT)-type SOI-FinFET flash memories, and confirmed that the TG structure has a larger memory window and a higher SCE immunity than the DG structure owing to the additional top gate and recessed buried oxide (BOX) region (21)(22)(23)(24). Moreover, we have also demonstrated FG-type split-gate SOI-FinFET flash memories with highly suppressed overerase and experimentally confirmed that nanosize triangular cross-sectional tunnel areas are useful for the fabrication of low-operating-voltage flash memories (25,26). However, the fin channel shape and interpoly dielectric (IPD) material effects on the electrical characteristics of FG-type SOI-FinFET flash memories have not been investigated sufficiently, although the high-k dielectric stacks and barrier-engineered multilayers have been used as an IPD layer for improving the gate coupling of the conventional bulk planar FG-type flash memories (27)(28)(29)(30).…”
Section: Introductionsupporting
confidence: 54%
“…Note that this RIE process was accompanied by the etching of the BOX region, i.e., the recessed BOX region was automatically formed. Then, an 8-nm-thick tunnel oxide (T ox ) layer was formed by thermal oxidation at 850 o C, followed by the deposition of a 30-nm-thick n + -polycrystalline silicon (n + -poly-Si) layer as the FG material by low-pressure chemical vapor deposition (LPCVD) at 580 o C. After the FG formation by EB lithography and RIE, a 3-nm-thick thermal SiO 2 layer was formed on the FG surface by rapid thermal oxidation (RTO) at 950 o C for 80 s (26). Then, a 5-nm-thick nitride (Si 3 N 4 ) layer was deposited by LPCVD at 790 o C for all the sample wafers.…”
Section: Device Fabricationmentioning
confidence: 99%
“…However, the blocking layer material effect on the electrical characteristics of SOI-FinFET flash memories has not been studied sufficiently. Very recently, we have demonstrated floating gate (FG) type split-gate fin-channel flash memories with a highly suppressed over erase, and experimentally confirmed that nanosize triangular cross-section tunnel areas are useful for the fabrication of the low operating voltage flash memories owing to the enhanced local electric field at the tips of triangular tunnel areas [35][36][37][38]. We have also fabricated and investigated FG type crystalline and polycrystalline Si fin-channel flash memories with DG and TG structures, and confirmed that TG structured flash memory shows the better SCE immunity and a larger memory window than the DG structured one owing to the additional top gate and recessed buried oxide (BOX) region [39][40][41].…”
Section: Introductionmentioning
confidence: 92%
“…31) For this reason, very recently, we have developed FG-type crystalline-Si fin-channel flash memories and demonstrated a splitgate fin-channel flash memory with highly suppressed overerase. [32][33][34][35][36][37] As further study, in this work, we fabricate scaled poly-Si fin-channel DG-and TG-type flash memories with a thin n þ -poly-Si FG, and systematically investigate the gate structure dependence of variability including V t and the S-slope before and after one P/E cycle.…”
Section: Introductionmentioning
confidence: 99%